2018
DOI: 10.1016/j.jaci.2017.08.043
|View full text |Cite
|
Sign up to set email alerts
|

IL-1/inhibitory κB kinase ε–induced glycolysis augment epithelial effector function and promote allergic airways disease

Abstract: Collectively, these findings demonstrate that IL-1β/inhibitory κB kinase ε signaling plays an important role in HDM-induced glycolysis and pathogenesis of allergic airways disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 64 publications
3
56
1
Order By: Relevance
“…Smallwood et al identified significant increases in glucose uptake in the lungs of pediatric patients infected with respiratory virus, and significant increases in glucose uptake and glycolytic flux occurring after influenza infection in primary human respiratory cells (13). In addition, elevated level of glycolysis and production of lactic acid were observed in asthmatic patients (17–19). Moreover, in the sputum of asthmatics the lactic acid level was positively correlated with sputum level of IL‐1β and negatively correlated with lung function of patients (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smallwood et al identified significant increases in glucose uptake in the lungs of pediatric patients infected with respiratory virus, and significant increases in glucose uptake and glycolytic flux occurring after influenza infection in primary human respiratory cells (13). In addition, elevated level of glycolysis and production of lactic acid were observed in asthmatic patients (17–19). Moreover, in the sputum of asthmatics the lactic acid level was positively correlated with sputum level of IL‐1β and negatively correlated with lung function of patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, elevated level of glycolysis and production of lactic acid were observed in asthmatic patients (17–19). Moreover, in the sputum of asthmatics the lactic acid level was positively correlated with sputum level of IL‐1β and negatively correlated with lung function of patients (18). Increased concentration of lactic acid may stimulate proliferating CD4 T cells, inhibition of glycolysis, and the increase of lactic acid attenuated airway inflammation and airway hyperreactivity in mouse model (18, 19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy metabolic pathway switch in asthmatic patients. Prior studies have shown that asthmatic patients had elevated serum and sputum levels of lactate and that cell from asthmatic patients produced higher amounts of lactate upon stimulation 28,29 . OVA sensitization and challenge upregulated glycolysis enzyme expression in rat lungs 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have reported that asthmatic patients had elevated serum and sputum levels of lactate and that cell from asthmatic patients produced higher amounts of lactate upon stimulation 28,29 , suggesting an enhanced glycolysis. However, these prior studies did not address the question whether the enhanced glycolysis is accompanied by a repressed OXPHOS activity (whether an energy metabolic pathway switch occurs).…”
Section: Discussionmentioning
confidence: 95%